2006
DOI: 10.1144/gsl.sp.2006.253.01.02
|View full text |Cite
|
Sign up to set email alerts
|

The numerical sandbox: comparison of model results for a shortening and an extension experiment

Abstract: Abstract:We report results of a study comparing numerical models of sandbox-type experiments. Two experimental designs were examined: (1) A brittle shortening experiment in which a thrust wedge is built in material of alternating frictional strength; and (2) an extension experiment in which a weak, basal viscous layer affects normal fault localization and propagation in overlying brittle materials. Eight different numerical codes, both commercial and academic, were tested against each other. Our results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
137
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(153 citation statements)
references
References 45 publications
14
137
0
2
Order By: Relevance
“…In their solution, the shear bands formed spontaneously and assumed various inclination angles ranging between the Roscoe and Coulomb limits. The results obtained with I2ELVIS (Gerya and Yuen, 2007) for the numerical sandbox experiment (Buiter et al, 2006) revealed that the majority of shear bands in the numerical solution tend to assume the Arthur angle. We conclude that our code is able to effectively simulate origination and propagation of localized shear zones.…”
Section: Initiation Of Shear Bands In the Brittle Crustmentioning
confidence: 94%
See 1 more Smart Citation
“…In their solution, the shear bands formed spontaneously and assumed various inclination angles ranging between the Roscoe and Coulomb limits. The results obtained with I2ELVIS (Gerya and Yuen, 2007) for the numerical sandbox experiment (Buiter et al, 2006) revealed that the majority of shear bands in the numerical solution tend to assume the Arthur angle. We conclude that our code is able to effectively simulate origination and propagation of localized shear zones.…”
Section: Initiation Of Shear Bands In the Brittle Crustmentioning
confidence: 94%
“…Arthur et al, 1977;Muhlhaus and Vardoulakis, 1987;Vermeer, 1990;Borja and Aydin, 2004;Buiter et al, 2006;Kaus and Podladchikov, 2006). One of the most important questions concerns preferred orientation of the shear bands.…”
Section: Initiation Of Shear Bands In the Brittle Crustmentioning
confidence: 99%
“…These models are typically non-linear and non-conservative, such that they can only be run forward (Buiter et al, 2006;Gray et al, 2014). The advantage of mechanical models in comparison to outcrop-or seismic-based models is that geometry, kinematics, stress, strain (incremental and total), and to some extent rock properties are known at any stage of the modelled evolution of the structure.…”
Section: Mechanical Modelsmentioning
confidence: 99%
“…The analog sandbox Buiter et al (2006) consists of a basal layer of weak, viscous silicone overlain by brittle sand. The sand 10 is extended by the movement of the right vertical wall and the connected basal plate extending from the wall to, initially, the centre of the domain.…”
Section: Model Set-upmentioning
confidence: 99%